Perception of Job Security In The Era of Artificial Intelligence Among Journalists In Ebonyi State, Nigeria - Adibe Nwafor, Kenneth; Chinasa Alegu, Johnson; Nsude, Ifeyinwa; Oketa, Chibugo; Nweze, Samuel; Francisca Nwakaego, Ede; Veronica Nkechi, Imakwu; Imakwu, Veronica Nkechi; Joy Anulika, Ogbu; O. Aleke, Christian (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
The advent of Artificial Intelligence (AI) has changed the way various jobs are done globally. In journalism, AI has been increasingly adopted in recent time in newsrooms, with tasks such as content generation, data analysis, and social media management being automated. This trend has sparked concerns among journalists all over the world, including Nigeria, particularly Ebonyi State, on the possibility of machines taking over their jobs in no distant time. This study investigated how practicing journalists in Ebonyi State, Nigeria, perceive the security of their job in the face of emerging era of AI. The objectives of the study were to ascertain the level of awareness of AI by practicing journalists in Ebonyi State, investigate the likely effects of AI on their job security, and evaluate their perception of job security in the era of AI. The study adopted the descriptive survey research design. Structured questionnaire was the instrument for data collection. A total of 280 practising journalist in Ebonyi state participated in the study. Data were collected using a structured questionnaire which had a consistency or reliability coefficient of 0.85. Analysis was done using descriptive statistics and summarised using frequency tables. Findings show that majority of the respondents did not feel that their jobs were at risk of being taken over by AI but that AI would complement them in their jobs and increase their productivity. The study concludes that journalists in Ebonyi State appear not to face immediate replacement by AI. The study recommends that Nigerian journalists particularly those in Ebonyi State should not be complacent with the current situation of things. Instead, they should acquire relevant skills that would make them to remain relevant in the era of Artificial Intelligence (AI).